Social identity in people with Multiple Sclerosis: an examination of family identity and mood - Barker, Alex B.; Lincoln, Nadina; Hunt, Nigel; das Nair, Roshan (Consortium of Multiple Sclerosis Centers, 2018)
Background: Mood disorders are highly prevalent in people with MS. MS causes changes to a person’s sense of self. The Social Identity Model of Identity Change posits that group membership can have a positive effect on mood during identity change. The family is a social group implicated in adjustment to MS. Objective: To investigate whether family identity can predict mood in people with MS. Methods: A cross-sectional survey design (n=123) comprising measures of family identity, family social support, connectedness to others, and mood. Results: Family identity predicted mood both directly and indirectly through parallel mediators of family social support and connectedness to others. Conclusion: Family identity predicted mood as posited by the Social Identity Model of Identity Change. Involving the family in adjustment to MS could reduce low mood.